2015
DOI: 10.1177/0284185114524090
|View full text |Cite
|
Sign up to set email alerts
|

The putaminal abnormalities on 3.0T magnetic resonance imaging: can they separate parkinsonism-predominant multiple system atrophy from Parkinson's disease?

Abstract: The signal changes in the putamen on T2W imaging on 3.0 T MRI, including slit-like hyperintense rim and putaminal hypointensity, are not specific signs for MSA-P. Putaminal atrophy is highly specific for differentiating MSA-P from PD and healthy controls, but its insufficient sensitivity limits its diagnostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 18 publications
4
25
0
Order By: Relevance
“…The sensitivity of this study was similar or slightly lower than those previously published for studies that used conventional fast spin-echo-based 3T MR imaging findings. 17,18 The sensitivity of our study was comparable with those of published studies that used T2*-weighted imaging. 19,20 By ROC curve analysis of the quantitative phase-shift values, sensitivity was increased to 77.8%, while specificity was slightly decreased (76.0%).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The sensitivity of this study was similar or slightly lower than those previously published for studies that used conventional fast spin-echo-based 3T MR imaging findings. 17,18 The sensitivity of our study was comparable with those of published studies that used T2*-weighted imaging. 19,20 By ROC curve analysis of the quantitative phase-shift values, sensitivity was increased to 77.8%, while specificity was slightly decreased (76.0%).…”
Section: Discussionsupporting
confidence: 79%
“…This finding was not clearly indicated by previous imaging studies, even those that used 3T imaging or 3T SWI. 18,23 Our quantitative measurement method was not a volumetric method and did not include all putaminal areas or consider the high-iron-deposition area that was proposed to be meaningful by previous publications. 11,13 Haacke et al 11 demonstrated that putative iron deposition in the high-iron-content region increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…1b) may also be observed in MSA [43]. Putaminal atrophy shows a high specificity (92.3%), but low sensitivity (44.4%) for distinguishing MSA- P from PD [44]. Meta-analysis of six studies (although heterogeneous) found putaminal volume to be significantly reduced in MSA patients versus PD, which may be helpful in the differential diagnosis [45].…”
Section: Magnetic Resonance Imaging In Parkinsonian Disordersmentioning
confidence: 99%
“…T2* visual grade was comparable in possible and probable MSA- C patients suggesting improved utility to support the diagnosis at earlier stages [46]. Another study compared the T2 appearances of the ‘putaminal rim sign’ and T2-putaminal hypointensities on a 3T scanner and found these to be unhelpful in distinguishing MSA- P , PD and controls [44]. However, a combination of T2-putaminal hypointensity on gradient-echo sequence together with putaminal atrophy improved the diagnostic specificity of MSA- P to 98% (versus PD) and 95% (versus PSP), without altering the sensitivity [47].…”
Section: Magnetic Resonance Imaging In Parkinsonian Disordersmentioning
confidence: 99%
“…Salvatore et al (2014) rely on T1 weighted MRI to differentiate PD from PSP, using Principle Component Analysis (PCA) for feature extraction and SVM for classification of diseases [15]. Feng et al (2014) [18]. Zanigni et al (2015) rely on MR Proton Spectroscopy (1H MRS) method for differential diagnosis between PD and other parkinsonian syndromes (MSA-C, MSA-P and Richardson syndrome (PSP-RS)).…”
Section: Introductionmentioning
confidence: 99%